Challenges and Difficulties in Implementing an Income-Contingent-Financing Model in Higher Education in Colombia (2022)
Background: One of the challenges of countries is offering higher education (HE) to populations that are not able to access it. The problem lies in the fact that many citizens are unable to finance the costs of their education. Some countries have implemented a system of financing that is contingent on income, seeking to improve the number of students entering HE and to increase access to educational financing; however, this system requires commitments from higher-education institutions, the country, and companies; thus, this text analyzes the challenges and difficulties regarding the implementation of the current system. Methods: Based on comparative international experience, an analysis of the political and social factors that hinder the implementation of ICF was conducted. This article focuses on countries with average development indexes that are on the verge of applying such a model, as is the case with Colombia. Results: From the economic point of view of the public and private sectors, an ICF model is justified in countries with different economic and social conceptions, and reforms for the implementation of ICF are given by the vision of the political and economic system that each country might have. Conclusion: International experience concludes that, for the ICF model to be successful, it should focus on its beneficiaries; that is, it should accurately identify the aspects of the users of educational credit. Furthermore, politicians must show prodigious leadership skills to effectively explain the economic logic of political leaders.